Program Evaluation Study on Islamic Religious Education in Pesantren: Addressing Educational Degradation in the Digital Era - Jamil, Zawaqi Afdal; Nurhuda; Alfian; Ulfah, Siti Mariah; Rasidin; Ahmed Youssef (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This study aims to evaluate the forms and underlying causes of educational degradation in pesantren (Islamic boarding schools) within the context of the digital era. It is to identify Islamic Boarding schools which are prepared to adopt technology in their teaching systems Design/methodology/approach – The study employed a program evaluation method using a formative evaluation model. Data collection and analysis were conducted through a mixed-methods approach. Quantitative data were gathered through questionnaires and analyzed using descriptive statistics, while qualitative data were collected through in-depth interviews and analyzed thematically. Findings – The evaluation results revealed that the average scores for the aspects related to educational degradation and its contributing factors were extremely low, at only 16.4% and 19.5%, respectively. These findings suggest that the limited use of technology in pesantren teaching reflects an institutional decline. This condition is attributed to inadequate infrastructure, low digital literacy, resistance to cultural change, and the absence of curricula and policies aligned with contemporary developments. The study highlights the urgent need for strategic interventions to enhance infrastructure, digital competence, and curriculum reform to prevent pesantren from falling further behind in the digital era. Research implications/limitations – The study implies that the low level of digital adoption necessitates strategic planning for infrastructure provision and teacher training to improve digital literacy. However, the study is limited in scope to the analysis of Islamic education degradation within pesantren. Future research should consider broader investigations using inferential statistical analysis to measure the impact of technology adoption across different pesantren contexts. Originality/value – This research offers a novel contribution by proposing a data-driven approach, the use of digital platforms, and innovation in teaching methods as practical solutions to ensure the continuity of Islamic education in pesantren without compromising its core spiritual values